2010
DOI: 10.1007/s12195-010-0123-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of B cell Synapse Formation by Monte Carlo Simulation Shows That Directed Transport of Receptor Molecules Is a Potential Formation Mechanism

Abstract: The formation of the protein segregation structure known as the “immunological synapse” in the contact region between B cells and antigen presenting cells appears to precede antigen (Ag) uptake by B cells. The mature B cell synapse consists of a central cluster of B cell receptor/Antigen (BCR/Ag) complexes surrounded by a ring of LFA-1/ICAM-1 complexes. In this study, we used an in silico model to investigate whether cytoskeletally driven transport of molecules toward the center of the contact zone is a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…BCR signaling is known to activate key activators of actin nucleation factors, which, in turn, may allow actin polymerization to actively drive the surface BCRs and facilitate their clustering. Recent modeling studies using stochastic simulations of the dynamics of BCR and LFA1 molecules suggest that the formation of the synapse occurs only if BCR mobility is enhanced by directed movement as might occur because of actin polymerization (34). These models and our observations together suggest that local BCR signaling to actin regulators lead to actin polymerization and directed motility of clusters, which facilitates BCR aggregation into larger clusters, enhancing signaling (25).…”
Section: Discussionsupporting
confidence: 66%
“…BCR signaling is known to activate key activators of actin nucleation factors, which, in turn, may allow actin polymerization to actively drive the surface BCRs and facilitate their clustering. Recent modeling studies using stochastic simulations of the dynamics of BCR and LFA1 molecules suggest that the formation of the synapse occurs only if BCR mobility is enhanced by directed movement as might occur because of actin polymerization (34). These models and our observations together suggest that local BCR signaling to actin regulators lead to actin polymerization and directed motility of clusters, which facilitates BCR aggregation into larger clusters, enhancing signaling (25).…”
Section: Discussionsupporting
confidence: 66%
“…For the purpose of calculating local concentrations of receptor-ligand complexes, the membrane surface is discretized into square subdomains over which membrane separation remains approximately constant. The spatially averaged concentration of receptor-ligand complexes in each of these subdomains is then calculated from the kinetic Monte Carlo model and entered in the discrete form of the membrane equation [44][45]. In our Monte Carlo model, memebrane separation is updated at the end of each MC time step by solving the membrane equation.…”
Section: Hybrid Simulation Methodsmentioning
confidence: 99%
“…Such a monotonically increasing response, however, is not obvious as low affinity antigens clearly have the ability to quickly dissociate from a B cell receptor and serially activate a large number of such receptors in a small amount of time. We use Monte Carlo simulations to explore the molecular mechanism of B cell affinity discrimination [36,[43][44][45][46].…”
Section: B Lymphocyte Activation and Antigen Affinity Discriminationmentioning
confidence: 99%
“…However, we did not thoroughly investigate the causes of affinity-dependent sub-diffusive motion, nor did we attempt characterize the motion or study its equilibrium behavior. In a separate study, we have shown that directed transport of receptors can be a mechanism for immunological synapse formation in B cells 40. However, in that work, the directed transport of receptors was not probed quantitatively through MSD plots.…”
Section: Introductionmentioning
confidence: 93%
“…Receptor–antigen complexes cluster at the center of the cell interface, surrounded by integrin–integrin complexes, forming the supramolecular activation complex known as the “immunological synapse,” a key step in the lymphocyte activation process 1,5,14,19,25,46. Diffusion of receptors and ligands (in this case, antigens and integrins) plays a crucial role in the formation of the immunological synapse 15,4042. During the initial phase immunological synapse formation, receptors form nanoscale micro-clusters on lipid raft domains, whose formation is also crucially modulated by diffusion of receptors and ligands 10,13,36,38…”
Section: Introductionmentioning
confidence: 99%